SEBARAN NILAI KAPASITAS TUKAR KATION (KTK) DAN KEMASAMAN (pH) TANAH DI TANAH VERTISOL KECAMATAN SAKRA KABUPATEN LOMBOK TIMUR - Sarah, Siti; AB, Baharuddin; Bustan, Bustan (Journal of Soil Quality and Management, 2024)
Abstract : this study aims to determine the distribution of Cation Exchange Capacity (CEC) and Acidity (pH) values ​​of soil. This research was conducted in December 2021 - January 2022. The location for taking soil samples was in Sakra District, East Lombok Regency, West Nusa Tenggara. Soil analysis was carried out in January 2021 at the Soil Chemistry Laboratory, Faculty of Agriculture, University of Mataram. The approach used in this study is the land unit (land unit). Soil samples in this study were taken by random sampling technique. The random sampling method is the process of taking samples using a random method. The sample points that will be used are 35 points representing vertisol soils in Sakra District. Soil sample data from the field is analyzed or tested in the laboratory. This laboratory test aims to determine the value of Cation Exchange Capacity (CEC) and Soil Acidity (pH). Utilization of Geographic Information Systems (GIS) in this research is by using the Arcgis application which is used to make maps. Maps are made by processing data that has been analyzed so that it can be entered and overlaid in the application. The results of the study showed that the CEC content analysis of this soil was classified as high, with medium to very high categories. Soil CEC at the study site ranged from 19.73 me/100gr to 69.62 me/100gr. Meanwhile, the results of the analysis of soil pH levels were classified as neutral, with a slightly acidic to slightly alkaline category. The pH level at the study site ranged from 6 to 8.4. Based on the results of research that has been done, this soil has a fairly good level of fertility, but it is necessary to add organic matter as a soil conditioner in order to maintain and increase soil fertility.